Citizen Science for Maine’s Classrooms: The Case for Improving STEM Learning - Voyer, Christine (Maine Policy Review, 2017)
Education, business, and community leaders recognize the need for increased emphasis on science, technology, engineering, and mathematics (STEM) education to prepare students for future careers and citizenship. STEM education best practices increasingly call for engaging students in doing the work of science, and citizen science offers an exciting opportunity for this type of teaching and learning. Maine has a unique opportunity, because of the size of our state and the number of research and education organizations engaged in citizen science, to offer citizen science experiences to a statewide cohort of students. Through this work, Maine can serve as a model to school districts, states, and regions for impactful and authentic STEM learning that reaches all students.